1995
DOI: 10.1136/vr.136.8.187
|View full text |Cite
|
Sign up to set email alerts
|

Critical features of veterinary field trials

Abstract: The field trials of drug and vaccine efficacy published in The Veterinary Record in the last five years were reviewed. The reviewers showed that in addition to some excellent studies with clear and concise design and analysis, there was a considerable lack of detail in reporting the method of allocation of animals to treatments, whether groups of animals or individual animals were allocated to treatments, whether the trials were blind, and a lack of formal analysis of the results. A considerable number of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Exposure to infectious agents probably results in a more-homogeneous serological status of animals within clusters as measured by the intra-cluster correlation coefficient (Donald and Donner, 1987;Rothman, 1990), because the interrelatedness of incidence and prevalence is the very characteristic that defines infectious diseases (Koopman et al, 1991;Susser, 1994a;De Jong, 1995). Consequently, it cannot be assumed that the animals are independent units (Schukken et al, 1991;Elbers and Schukken, 1995;Cameron and Baldock, 1998), because compared to other population members, animals within clusters have a higher chance of becoming infected once the infection is introduced into the herd.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to infectious agents probably results in a more-homogeneous serological status of animals within clusters as measured by the intra-cluster correlation coefficient (Donald and Donner, 1987;Rothman, 1990), because the interrelatedness of incidence and prevalence is the very characteristic that defines infectious diseases (Koopman et al, 1991;Susser, 1994a;De Jong, 1995). Consequently, it cannot be assumed that the animals are independent units (Schukken et al, 1991;Elbers and Schukken, 1995;Cameron and Baldock, 1998), because compared to other population members, animals within clusters have a higher chance of becoming infected once the infection is introduced into the herd.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the availability of these criteria, the quality of reporting of intervention trials remains poor. An assessment of the quality of RCTs published in one journal revealed that although some of the trials provided information on methodological features, many others failed to do so (Elbers and Schukken, 1995). These trials lacked information related to the method of treatment allocation, the grouping of animals relative to treatment allocation, the use or non-use of blinding and the method of statistical analysis (Elbers and Schukken, 1995).…”
Section: Incomplete and Inaccurate Reporting In Published Livestock Imentioning
confidence: 99%
“…An assessment of the quality of RCTs published in one journal revealed that although some of the trials provided information on methodological features, many others failed to do so (Elbers and Schukken, 1995). These trials lacked information related to the method of treatment allocation, the grouping of animals relative to treatment allocation, the use or non-use of blinding and the method of statistical analysis (Elbers and Schukken, 1995). Further, several systematic reviews in pre-harvest food safety (Denagamage et al, 2007;O'Connor et al, 2008) and animal health (O'Connor et al, 2006;Wellman and O'Connor, 2007;Burns and O'Connor, 2008) have noted a lack of reporting of group allocation methods; blinding and details related to intervention protocols, outcome assessments and statistical analysis methods in some published clinical trials.…”
Section: Incomplete and Inaccurate Reporting In Published Livestock Imentioning
confidence: 99%
“…However, previous studies have illustrated substantive issues related to the reporting of clinical trials in the small animal literature 1 and in veterinary medicine in general. 2 Authors of systematic reviews of therapeutic interventions in dogs and cats also have reported shortcomings in the reporting of key features in the published research. [3][4][5][6] Numerous studies have reported shortcomings in the reporting of important methodological features of clinical trials in human clinical research.…”
mentioning
confidence: 99%